2020
DOI: 10.1111/cas.14493
|View full text |Cite
|
Sign up to set email alerts
|

Statins use and its impact in EGFR‐TKIs resistance to prolong the survival of lung cancer patients: A Cancer registry cohort study in Taiwan

Abstract: Statins have been shown to be a beneficial treatment as chemotherapy and target therapy for lung cancer. This study aimed to investigate the effectiveness of statins in combination with epidermal growth factor receptor‐tyrosine kinase inhibitor therapy for the resistance and mortality of lung cancer patients. A population‐based cohort study was conducted using the Taiwan Cancer Registry database. From January 1, 2007, to December 31, 2012, in total 792 non‐statins and 41 statins users who had undergone EGFR‐TK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 47 publications
1
18
0
Order By: Relevance
“… 52 A study that focused on the relationship of statin use and survival in patients with lung cancer who received Epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKI) therapy, showed greater age disparities in the statin group than in the non-statin group. 69 …”
Section: Resultsmentioning
confidence: 99%
“… 52 A study that focused on the relationship of statin use and survival in patients with lung cancer who received Epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKI) therapy, showed greater age disparities in the statin group than in the non-statin group. 69 …”
Section: Resultsmentioning
confidence: 99%
“…Recent clinical studies have shown that high-intensity statins are associated with improved clinical activity of PD-1 inhibitors, and the combined application can improve the prognosis of patients with malignant pleural mesothelioma and advanced non-small cell lung cancer [ 69 ]. A recent cohort study from Taiwan has shown that statins are associated with increased survival in lung cancer patients treated with epidermal growth factor receptor-tyrosine kinase inhibitors (EGFR-TKIs) and exert synergistic anti-cancer effects [ 304 ]. Similarly, another cohort study of 1,835 patients with gastric cancer from Taiwan, suggested that the statin use improves the overall survival of patients with gastric cancer after surgery and adjuvant chemotherapy [ 60 ].…”
Section: Maximizing Efficacy and Addressing Shortcomings Of Conventional Cancer Therapymentioning
confidence: 99%
“…Third, the epidermal growth factor receptor (EGFR), which is associated with hepatoma-related virus infections involving viruses such as HBV and HCV, is involved in the association of coronavirus with ILD and pulmonary fibrosis (eg, IPF). 22 23 Nguyen et al 24 reported that statins may play a supportive role in attenuating the effect of EGFR overexpression in patients with cancer. Collectively, the aforementioned findings indicate that statins are associated with a lower risk of immunological cancers in patients with ILD and pulmonary fibrosis, which are closely associated with virus infections.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%